Study on Cyanate Ester Resin Modified with Epoxy Group Silane - Li, Qian; Wang, Xiang-Ting (Asian Journal of Chemistry, 2015)
Bisphenol A dicyanate ester (BCE) was modified with epoxy group silane i.e., g-(2,3-epoxypropoxy)propyl silane (ESi) to improve impact strength of pure resin. The results showed the mechanical properties were improved mainly by the reaction of epoxy group in g-(2,3-epoxypropoxy)propyl silane and cyanate group in bisphenol A dicyanate ester. The morphology of the cured materials was investigated by scanning electron microscopy techniques. The ESi/BCE composites were shown to have better impact strength and flexural strength properties. When the value of Tg is not significantly changed, impact and flexural strength of modified resins were increased from 10.1 kJ/m2 and 94.11 MPa to 14.49 kJ/m2 and 123.93 MPa, respectively.